Karakteristik Vegetasi Habitat Surili (Presbytis comata) di Kawasan Gunung Subang desa Legokherang Kecamatan Cilebak Kabupaten Kuningan (hal 38-46) - Toto Supartono; Asep Budi Wahyono; Ai Nurlaila (Wanaraksa, 2014)
The aim of the research is to identify woody plants, diversity of Presbytis comata habitat, the existence of Presbytis comata feed and physical state of the mount ring. Vegetation data collected by using transek method and analyzed by counting Shannon-Wiener Diversity Index. Observation areas and spatial data analysis done to see the physical condition of the Presbytis comata habitat. The vegetation found 67 plant species are woody and 31 types expressed as Presbytis comata feeds. Presbytis comata feed mostly consists of the moraceae family. Types of Presbytis comata habitat in the Subang area is lowland tropical rainforest type with an elevation of 625-1200 m above sea level. The slope of mountain in Subang areas very varies from flat, sloping, somewhat steep, to very steep.Keywords: Presbytis comata, habitat, woody plants diversity